Gender Transformative Education in Zimbabwe’s Fast-Track Land Resettlement schools: Reimagining Gender norms and Social Inclusion - Muchabaiwa, Wonder; Moyo, Annah (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Many developing countries continue to battle with issues of social inclusion, gender equity, and equality in primary and secondary schools. For Zimbabwe, the Fast-Track Land Reform Programme (FTLRP) executed in 2000 ushered a problematic context that exacerbated social exclusion and gender inequalities in Education.  The unplanned, politically motivated, and hastily executed FTLRP created disruptive learning environments affecting female and male students disproportionately.  This study aimed to investigate how the FTLRP hindered opportunities for gender-transformative education in fast-track resettlement schools. It also aimed to promote social inclusion and gender justice in rural fast-track resettlement schools. The study adopted a participatory qualitative approach to triangulate data from in-depth interviews, observations, and desk reviews of curricula materials. It also adopted intersectionality feminism lens to illuminate gender dynamics in fast-track resettlement schools. Such a holistic approach provided critical insights into how gender overlaps with poverty and rurality to diminish opportunities for gender-transformative education. Findings show that poor infrastructure in the fast-track resettlement schools continues to obstruct gender-transformative education. Teachers are not conversant with gender-responsive pedagogies, let alone gender-transformative education practices. It also reveals that informal boarding facilities in fast-track resettlement schools are havens for sexual harassment. The study concludes that the FTLRP in Zimbabwe created disruptive learning environments that continue to obstruct initiatives for gender justice and social inclusion in schools. Female students tend to suffer from social exclusion because of their gender, poverty and rurality. Conducting a gender audit in fast-track resettlement schools would help in developing a robust gender-transformative education policy framework.